Workgroup diversity: surface-level actual similarity and deep-level perceived similarity in leader-member relationship communication - Abu Bakar, Hassan; McCann, Robert M. (Emerald Publishing Limited, 2018)
Purpose – The purpose of this paper is to explore whether surface-level actual similarity interacts with leader-member dyadic communication agreement in predicting group member performance ratings at earlier time periods in a work group’s development. Additionally, this research examines whether deep-level perceived similarity interacts with leader-member dyadic communication agreement in predicting group member performance ratings at later time periods in a work group’s development. The relationship between shared cultural context and perceived and actual similarity is also investigated. Design/methodology/approach – This research analyzes longitudinal data from the study questionnaires at five occasions in a Malaysian organization. Findings – Results based on a sample of 28 group projects and 141 matching dyad who completed the study questionnaires at 5 occasions reveal that there is no interaction between workgroup relational ethnicity and workgroup relational gender with leader-member dyadic agreement at early time periods in a workgroup’s development. Therefore, H1 is not supported. H2 posited that deep-level perceived similarity will interact with leader-member dyadic communication agreement in predicting group member performance ratings at later time periods in a workgroup’s development. H2 is supported. Results reveal that the interaction between leader-member dyadic communication agreement and perceived similarity explains 36 percent of the variance of perceived group members’ performance ratings. This is after accounting for the control variable and the independent variables. From a cultural standpoint, the findings in this study underscore that conversations based on the Malaysian cultural norm of “budi” reflect not only a cultural basis of communication, but also that this shared cultural context leads to perceived similarity between ethnic Malay, Chinese, and Indians, and also both genders in the Malaysian workplace. Research limitations/implications – Leader-member dyadic communication agreement reflects the social appropriateness and relationship quality between individuals, as well as the context of the leader-member workgroup interactions. The findings of this study underscore the premise that conversations reflect not only a cultural basis of communication, but also that shared cultural context leads to perceived similarity. This study specifically examines the role of ethnicity in Malaysia organizational workgroup (e.g. ethnic Malay, Chinese Malay, and Indian Malay) as well as gender. Originality/value – This study systematically examines the influence of actual and perceived similarity in leader-member dyadic communication from a longitudinal and multilevel standpoint.